Xilinx FPGA based multilevel PWM single phase inverter - Mekhilef, Saad; Masaoud, A. (2006)
In this paper a XILINX FPGA based multilevel PWM single-phase inverter was constructed by adding a bidirectional switch to the conventional bridge topology. The inverter can produce three and five different output voltage levels across the load. XILINX FPGA is a programmable logic device developed by XILINX which is considered as an efficient hardware for rapid prototyping. It is used as a PWM generator to apply the appropriate signals to inverter switches. In addition to XILINX FPGA, Matlab/Simulink software was used for simulation and verification of the proposed circuit before implementation, Simulation and experimental results show that both are in close agreement.